Late Devonian paleomagnetic age for the Polaris Mississippi Valley-type Zn–Pb deposit, Canadian Arctic Archipelago (Dataset) ... - D. T. A. Symons; D. F. Sangster (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Late Devonian paleomagnetic age for the Polaris Mississippi Valley-type Zn–Pb deposit, Canadian Arctic Archipelago ...